2020
DOI: 10.1111/bpa.12886
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β/IL‐1R1 signaling induced by intranasal lipopolysaccharide infusion regulates alpha‐Synuclein pathology in the olfactory bulb, substantia nigra and striatum

Abstract: Olfactory dysfunction is one of the early symptoms seen in Parkinson’s disease (PD). However, the mechanisms underlying olfactory pathology that impacts PD disease progression and post‐mortem appearance of alpha‐Synuclein (α‐Syn) inclusions in and beyond olfactory bulb in PD remain unclear. It has been suggested that environmental toxins inhaled through the nose can induce inflammation in the olfactory bulb (OB), where Lewy body (LB) is the first to be found, and then, spread to related brain regions. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…Studies herein where initiated because we had observed regionally specific anomalous PSER129 signal in untreated healthy wildtype mice. Interestingly others have observed this mitral cell staining phenomenon but not realized the significance 27 . We demonstrated that the anomalous PSER129 signal was likely an endogenous PSER129 population sensitive to PK digestion that occurred in the mitral cells of healthy mammals.…”
Section: Mitral Cells In Synucleinopathiesmentioning
confidence: 90%
“…Studies herein where initiated because we had observed regionally specific anomalous PSER129 signal in untreated healthy wildtype mice. Interestingly others have observed this mitral cell staining phenomenon but not realized the significance 27 . We demonstrated that the anomalous PSER129 signal was likely an endogenous PSER129 population sensitive to PK digestion that occurred in the mitral cells of healthy mammals.…”
Section: Mitral Cells In Synucleinopathiesmentioning
confidence: 90%
“…In addition, activated microglia have been associated with reduced autophagy, further contributing to a-syn aggregation. The deletion of IL-1R1 inhibited the transmission of a-syn and TH-positive cell loss (70). NLRP3 activation promotes the secretion of the inflammatory cytokine interleukin-1b/18 (IL-1b/18) and induces pyroptosis, a type of cell death that possesses the potential for inflammation, to rupture microglia to further release IL-1b (71).…”
Section: The Activation Of Nlrp3 Inflammasome In Pdmentioning
confidence: 99%
“…A recent study using intranasal infusion of endotoxin-lipopolysaccharide (LPS) to induce olfactory bulb (OB) inflammation in mice found that LPS triggered microglial activation, inflammatory cytokine expression, and phosphorylated αSyn accumulation in the OB and SN through IL-1β/IL-1 receptor 1-dependent signaling. 100 This finding suggests that inflammation, particularly IL-1, plays a role in mediating the initiation and propagation of αSyn pathology from the OB. 100 In relation to systemic inflammation, La Vitola et al 101 developed a PD mouse model through systemic administration of LPS followed by intracerebroventricular injection of an αSyn oligo-mer as well as an αSyn-overexpression transgenic mouse administered LPS.…”
Section: Jmdmentioning
confidence: 99%
“…100 This finding suggests that inflammation, particularly IL-1, plays a role in mediating the initiation and propagation of αSyn pathology from the OB. 100 In relation to systemic inflammation, La Vitola et al 101 developed a PD mouse model through systemic administration of LPS followed by intracerebroventricular injection of an αSyn oligo-mer as well as an αSyn-overexpression transgenic mouse administered LPS. The authors demonstrated that peripherally induced neuroinflammation influences the action of αSyn oligomers to potentiate a detrimental effect.…”
Section: Jmdmentioning
confidence: 99%